Implementation of the Independent Curriculum with Islamic Religious Education to Develop Soft Skills Student - Siti Rahmawati; Fauziyah Qurrota A’yun Tamami; Mahmudulhassan Mahmudulhassan; Sabrina Failasufa Tamami (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
This study explores the implementation of the Independent Curriculum at SMP Muhammadiyah 2 Makamhaji Kartasura known as